2013
DOI: 10.1111/joim.12082
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in bile acid synthesis in carriers of hepatocyte nuclear factor 1α mutations

Abstract: Objectives. Heterozygous mutations in hepatocyte nuclear factor 1a (HNF1a) cause maturity onset diabetes of the young 3 (MODY3), an autosomal dominant form of diabetes. Deficiency of HNF1a in mice results in diabetes, hypercholesterolaemia and increased bile acid (BA) and cholesterol synthesis. Little is known about alterations in lipid metabolism in patients with MODY3. The aim of this study was to investigate whether patients with MODY3 have altered cholesterol and BA synthesis and intestinal cholesterol abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
(67 reference statements)
2
11
0
3
Order By: Relevance
“…HNF1α defect in humans is associated with increased bile acid synthesis[7] and influences levels of total cholesterol, high density cholesterol and low-density lipoprotein[8], [34]. These effects are likely mediated through regulation of multiple hepatic genes, such as the hepatic lipase promoter gene [35], Niemann-Pick C1-like 1 ( NPC1L1 ) and Acyl-CoA: cholesterol acyltransferase-2 ( ACAT-2 ) [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNF1α defect in humans is associated with increased bile acid synthesis[7] and influences levels of total cholesterol, high density cholesterol and low-density lipoprotein[8], [34]. These effects are likely mediated through regulation of multiple hepatic genes, such as the hepatic lipase promoter gene [35], Niemann-Pick C1-like 1 ( NPC1L1 ) and Acyl-CoA: cholesterol acyltransferase-2 ( ACAT-2 ) [36].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major manifestations of HNF1α defect in humans is β-cell dysfunction that impairs glucose-induced insulin secretion[5],[6]. HNF1α defect in humans is also associated with increased bile acid synthesis[7], and influences levels of total cholesterol and low-density lipoprotein[8]. Studying carriers of HNF1α defects could therefore contribute to a better understanding of diabetes pathophysiology and related metabolic pathways, and open doors to develop new therapies for this disease that now affects about 12–14% of the USA population and is predicted to continue to increase in prevalence in the coming years[9].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D protein structure prediction has shown that the T260 was in the DNA-binding domains and the mutation T260M destabilize the protein, which indicates that the function of the protein has been affected and induced the diabetes. By Cotransfection experiments, Ekholm et al showed that p.T260M mutation reduced the induction of the farnesoid X receptor (FXR) promoter and reduced the induction of the apical sodium-dependent bile salt transporter promoter [24], which indicated that p.T260M mutation leads to the functional changes of related gene. Three HNF1A isoforms were affected when the mutations were located in exon 1–6, and the diagnosis age of diabetes were younger than those with missense mutations involving one or two isoforms [25].…”
Section: Discussionmentioning
confidence: 99%
“…The condition may also be associated with hepatic adenomatosis, bile acid synthesis alteration, decreased pancreatic volume, pancreatic dysfunction and other diseases [37,38,[55][56][57][58]. The patients also have elevated urinary glucose due to low renal threshold for glucose in this genetic subtype [59].…”
Section: Modymentioning
confidence: 99%
“…• detectable C-peptide more than 0.2 nmol/l outside the honeymoon period, GST more than 0.2 nmol/l [22,27], • Presence of liver pathology particularly both benign and malignant primary liver cell tumors (liver adenomatosis, hepatocellular carcinoma) [35][36][37][38][39][40]. During pregnancy body mass index (BMI) <25 kg/m 2 and fasting glucose ≥5.5 mmol/L can also be used as separate indicators of GCK mutation and has a sensitivity of 68% and 96% specificity.…”
Section: Mody Features and Diagnosismentioning
confidence: 99%